Survei Tingkat Keterampilan Shooting Dalam Permainan Sepak Bola Ekstrakulikuler SMA Negri Balung - Moh Abdul Rohman; Rizki Apriliyanto; Wahyu Eko Widiyanto (Jurnal Porkes, 2026)
Shooting skills are a crucial fundamental technique in soccer because they are a determining factor in a team’s success in scoring goals. However, the soccer players in the Balung State High School extracurricular program have never been scientifically evaluated regarding their shooting skill levels based on their playing positions, making it difficult for coaches to design targeted training programs tailored to the players’ needs. This study aims to analyze the shooting skill levels of the Balung State High School soccer club players based on their playing positions. The method used was a descriptive survey with a quantitative approach. The sample consisted of 30 players selected using purposive sampling, with the criteria being that they were active players who trained regularly. Data collection was conducted through a shooting test toward the goal from a distance of 16.5 meters, consisting of three attempts, with a maximum score of 15 points. The data were analyzed using descriptive statistics. The results showed that the overall average shooting skill of the players was 7.43 (49.56%), falling into the “fair” category. The striker position achieved the highest average (8.44 or 56.30%), followed by defenders and midfielders with the same average (7.44 or 49.63%), while goalkeepers had the lowest average (4.33 or 28.89%). The conclusion of this study is that the shooting skills of the extracurricular soccer players at Balung State High School vary depending on their playing positions and, in general, are still in the “adequate” category.